Defining treatment effects: A regulatory perspective. (August 2019) - Permutt, Thomas
The proposed addendum to the International Conference on Harmonization document, Statistical Principles for Clinical Trials, can be read in two ways. There is a new framework for talking about estimands, but is it about fitting present methods into the framework? Or is it about changing methods? My answer: some of each. Where different methods are needed, there are challenging problems in estimating some desirable estimands, but there may also be desirable estimands that can be estimated easily and robustly.